Analisis Yuridis Peran Informed Consent dalam Penghapusan Pertanggungjawaban Pidana bagi Tenaga Medis - Utari Sastrani , I Dewa Ayu Nyoman (Journal Evidence Of Law, 2025)
This research analyzes the juridical role of informed consent in eliminating criminal liability for medical professionals in Indonesia. Through a normative-juridical approach with descriptive-qualitative analysis methods, this study examines the legal framework of informed consent and its function as grounds for eliminating criminal liability. Informed consent gains normative legitimacy through various legislation, including Law Number 36 of 2009 on Health and Minister of Health Regulation Number 290/Menkes/Per/III/2008 on Medical Treatment Consent. The results reveal that valid informed consent can be constructed as a justification that eliminates the "unlawful" element in criminal offenses based on the principle of volenti non fit iniuria. The validity of informed consent is determined by three fundamental parameters: quality of information provided, voluntarism of consent, and patient capacity. The protective function of informed consent has significant limitations, including its inability to eliminate criminal liability when medical actions violate professional standards, exceed the scope of consent, are based on inaccurate information, or contradict public order. This research recommends a comprehensive strategy encompassing regulatory harmonization, procedural standardization, capacity development, and implementation of electronic documentation systems to optimize the protective function of informed consent for medical professionals.